A method for manufacturing a multilayer composite soft ferrite core

Through the multi-layer composite soft ferrite core manufacturing method, casting technology and sintering process suitable for the atmosphere, the performance deterioration caused by the difference in sintering process in composite ferrite magnets is solved, and the high frequency and wide temperature range is achieved Excellent magnetic characteristics and low power consumption characteristics.

CN113936893BActive Publication Date: 2025-01-10TIANTONG KAILI TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111180827.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-11
Publication Date
2025-01-10
Estimated Expiration
2041-10-11

AI Technical Summary

Technical Problem

In the process of preparing composite ferrite magnets, it is difficult to reasonably control the differences in sintering process between different composite material components, resulting in deterioration of performance, especially in high frequency and wide temperature ranges, low power consumption and high magnetic characteristics are difficult to maintain.

Method used

Using a multi-layer composite soft ferrite core manufacturing method, the MnZn-type and NiZn-type soft ferrite green tapes were prepared by casting technology, and sintered under respective suitable atmospheres, and the main formula of the secondary layer was adjusted. The sub-format and arrangement method are stacked into multiple composite layers for bonding and warm pressing to make magnetic cores to avoid the problem of mismatch in the atmosphere.

Benefits of technology

It realizes high saturation magnetic induction strength and high magnetic permeability in high frequency and wide temperature ranges, avoids the problem of uneven performance, has the characteristics of design flexibility and high customization, and is suitable for the preparation of large-size magnetic cores.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113936893B_ABST
    Figure CN113936893B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a multi-layer composite soft ferrite core, and relates to the technical field of composite soft ferrite manufacturing. The magnetic core prepared by the method of the present invention is formed by stacking soft ferrite composite layers; a single soft ferrite composite layer is composed of soft ferrite secondary layers with different magnetic properties, and its electrical properties are determined by the electromagnetic properties of the composite layer, so it can be adjusted by changing the main formula and sub-formula of the soft ferrite material of the secondary layer in the composite layer, and the same purpose can also be achieved by adjusting the arrangement of the secondary layer and the proportion of the composite layer. Several secondary layers are bonded, and the composite soft ferrite core of the present invention is prepared by pressing, punching, and heat treatment curing. The ferrite core prepared by the method of the present invention can solve the problem of difficult mutual dissolution of multiple components and large differences in co-firing atmosphere in the traditional oxide method for preparing composite soft ferrite materials, and can be combined and designed according to performance requirements to expand the application field of materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite soft ferrite material manufacturing, and in particular relates to a method for preparing a composite magnetic core of MnZn ferrite and NiZn ferrite. Background Art

[0002] With the advancement of science and technology and the improvement of people's living standards, soft ferrite materials, as an important basic functional material, are widely used in electronic industries such as communications, filters, audio and video equipment, sensors, transformers, etc., and have broad market prospects. With the miniaturization and high frequency of device design, the development of single-component ferrite materials is challenged. Often, there are contradictions between various electromagnetic properties at the beginning of material design. For example, high Bs power ferrites often need to use a high iron content formula and introduce Ni in the main formula. + The design of increasing Tc will cause a significant deterioration in power consumption. It is difficult to maintain low power consumption in a wide temperature range. When improving a certain performance, other performances will often deteriorate. Therefore, the research direction of ferrites is gradually developing towards composite soft ferrite materials. For example, NiZn ferrites have good high-frequency characteristics, but Bs and μ i Relatively low, MnZn ferrite has good low frequency characteristics, Bs, μ i The upper limit is higher than that of NiZn ferrite, but the cut-off frequency is lower. By combining the two and complementing each other's advantages, a high Bs and high μ with a wider application frequency range can be obtained. i Ferrite.

[0003] However, the main problem in the manufacturing process of composite soft ferrites is that the sintering processes between different composite material components are quite different, making it difficult to reasonably control them. For example, NiZn ferrite is sintered in an oxidizing atmosphere, and MnZn ferrite needs to be sintered in a balanced atmosphere due to the Mn valence problem, which makes it difficult to design suitable sintering conditions to meet the atmospheres of both. Therefore, at present, only a small amount of NiO can be added to MnZn ferrite to improve the Bs characteristics, or a small amount of MnO can be added to NiZn ferrite to improve the high-frequency resistance. However, this modification method can only play a limited role. As too many composite components are added, the performance deteriorates sharply, which is particularly difficult to control during large-scale production.

[0004] The patent with publication number CN103632794A discloses a composite soft magnetic material and a method for preparing the material. The composite soft magnetic material is composed of soft ferrite powder and soft magnetic alloy film, and the soft magnetic alloy film is coated on the surface of the soft ferrite particles to form a film with a thickness of 0.01μm-10μm. The material obtained by sintering the obtained composite soft magnetic particles not only has a high saturation magnetic induction intensity, but also has a high magnetic permeability, and has the characteristics of soft ferrite and metal soft magnetic materials. At the same time, the material also has good mechanical properties and is mainly used in medium and high frequency fields. The method starts with powder for compounding, and the ferrite powder is coated with a metal material to obtain a composite electromagnetic property, but the method actually adopts a chemical plating process, and ferriteization still needs to be achieved through sintering in the future, and the problem of co-firing of the composite layer under unsuitable conditions cannot be avoided.

[0005] The patent with publication number CN103765524B discloses a composite material including a grain component and a nanostructured grain boundary component. The grain boundary of the nanostructure is insulated and magnetic so as to provide greater magnetization continuity of the composite material. The grain component has an average grain size of about 0.5 to 50 microns. The grain boundary component has an average grain size of about 1 to 100 nanometers. The nanostructured magnetic grain boundary material has a magnetic flux density of at least about 250mT. The grain component may include MnZn ferrite particles, and the nanostructured grain boundary component may include NiZn ferrite nanoparticles. The patent reduces eddy current losses by distributing NiZn ferrite with high resistivity at the grain boundaries, and also plays a role in improving Bs, but it is well known in the industry that NiZn ferrite has high resistivity. The difficulty of this method lies in how to make the NiZn grain boundary phase better distributed around the periphery of the MnZn grains. The patent uses a mixture of nano NiZn ferrite powder and MnZn ferrite powder, which is then sifted and then co-fired under nitrogen. However, the problem of inappropriate sintering conditions for MnZn and NiZn ferrite cannot be avoided.

[0006] The patent publication with the publication number CN111584206A provides a magnetic core and its preparation method, an inductor and a filter, which relates to the technical field of anti-EMI magnetic core and inductor components. The magnetic core is mainly formed by overlapping and winding a plurality of composite magnetic material layers; a single composite magnetic material layer includes a magnetic strip and an adhesive layer; at least one composite magnetic material layer is a composite magnetic material layer obtained after unitization; at least two composite magnetic material layers have different magnetic properties. This patent manufactures anti-EMI magnetic cores by bonding and winding strips with different magnetic properties available on the market. This is different from the present invention which starts from a more fundamental magnetic sheet manufacturing technology and regulates the performance of the secondary layer magnetic sheets by adjusting the main formula and sub-formula, pre-firing process, pulping, cast sheet sintering and other wider ranges. After bonding, the blanks are first hot pressed and then the finished magnetic cores are prepared by punching or multi-wire cutting process. The shape of the magnetic cores is more selective. The winding method described in patent CN111584206A is limited by the shape of the winding tooling and cannot produce flat or complex-shaped magnetic cores, so it is limited to circular ring-shaped magnetic cores for filtering.

[0007] In summary, in the process of preparing composite ferrite magnets in the prior art, there are still problems such as large differences in sintering processes between components of different composite materials, which are difficult to reasonably control. Therefore, the present invention adopts a method for manufacturing a multi-layer composite soft ferrite core, which can avoid the performance deterioration caused by atmosphere mismatch caused by co-firing of multiple components in the traditional composite method, and can also develop materials with excellent frequency characteristics, high Bs, and high magnetic permeability through flexible adjustment of formula and process. Summary of the invention

[0008] The present invention applies the tape casting technology to the preparation process of the composite ferrite soft magnetic material, and casts two or more soft ferrite green strips with a certain thickness respectively, which can be sintered in their respective suitable atmospheres, thereby avoiding the performance deterioration caused by the atmosphere mismatch caused by the co-firing of multiple components in the traditional composite method.

[0009] The present invention is mainly achieved through the following technical solutions:

[0010] A multilayer composite soft ferrite core is formed by stacking two or more soft ferrite composite layers. A single soft ferrite composite layer is composed of two or more soft ferrite secondary layers. The electromagnetic properties of the composite layer can be adjusted by changing the main formula and sub-formula of the soft ferrite secondary layer in the composite layer, the manufacturing process of the secondary layer ferrite pre-sintering material, the arrangement of the secondary layer and the proportion of the composite layer, thereby further improving the electromagnetic properties of the core. The preparation method has the characteristics of high design flexibility and customization.

[0011] The preparation method of the multilayer composite soft ferrite core is as follows: first, two or more ferrite secondary layers are prepared, which are formed after molding, sintering and laminating processes, then, the two or more secondary layers are bonded to obtain a soft ferrite composite layer, the two or more soft ferrite composite layers are stacked and pressed into a blank, and finally, the blank is punched or cut, heat-treated and cured to prepare a multilayer composite soft ferrite core.

[0012] A specific method for preparing a multi-layer composite soft ferrite core is to first determine two or more ferrite secondary layers, and then prepare the core according to the following method, including:

[0013] (1) Preparing ingredients according to the main formula and sub-formula of the ferrite secondary layer;

[0014] (2) respectively wet-mixing the main formula powders and then drying them to obtain ferrite dried materials;

[0015] (3) pre-calcining the dried ferrite obtained in step (2) in an air atmosphere at a temperature of 800° C. to 1000° C. for 2 h to 4 h, and cooling to room temperature in the furnace to obtain a ferrite pre-calcined material;

[0016] (4) The ferrite pre-fired materials pre-fired in step (3) are respectively subjected to ball milling, and a mixed solvent of alcohol and ethylbenzene is added in a mass ratio of solute to solvent of 5:4. After ball milling for 2 hours, a dispersant, a plasticizer, and a binder are added, and then the sub-formula components are added and ball milled together with the main formula for 6 hours to 10 hours. Dibutyl diformate plasticizer, triethanolamine dispersant and polyvinyl butyral binder are added to prepare a slurry with a viscosity of 40000 mPa.s to 60000 mPa.s, and the ball milling time is controlled to make the particle size distribution D50: 1 μm to 2.5 μm;

[0017] (5) preparing the ferrite slurry into ferrite green tapes with a smooth surface and a thickness of 0.1 mm to 0.5 mm by a tape casting process;

[0018] (6) sintering the ferrite green strips respectively, heating to 900°C to 1300°C at a rate of 3°C / min to 5°C / min, and then keeping the temperature for 2h to 6h, with the oxygen partial pressure of 2vol% to 20vol%, and cooling to below 200°C at a cooling rate of 2°C / min to 4°C / min by balanced oxygen partial pressure, to obtain two or more ferrite secondary layer magnetic sheets;

[0019] (7) coating and splitting the ferrite secondary layer magnetic sheet blanks sintered in step (6) to obtain two or more ferrite secondary layer magnetic sheets;

[0020] (8) bonding two or more ferrite secondary layer magnetic sheets obtained in step (7) with an adhesive to obtain a ferrite composite layer, stacking the two or more composite layers together, and pressing them into a composite soft ferrite blank plate by bidirectional warm pressing;

[0021] (9) The composite soft ferrite blank sheet obtained in step (8) is punched or cut into a magnetic core, and then subjected to a heat curing treatment to obtain a multilayer composite ferrite magnetic core.

[0022] As a preference, the ferrite secondary layer may be MnZn ferrite or NiZn ferrite.

[0023] As a preferred method, in the process of preparing the MnZn ferrite secondary layer, in step (1), the main formula is calculated by molar ratio as follows: Fe2O3: 48mol% to 58mol%; ZnO: 3mol% to 25mol%; the balance is Mn3O4, and the sub-formula components can be one or more of SnO2, CaO, TiO2, ZrO2, SiO2, V2O5, and Nb2O5;

[0024] In step (2), deionized water is added in a mass ratio of 1:1, and an amino dispersant is added to mix the oxides evenly to prevent agglomeration, and the mixing time is 15 min to 30 min; the mixture is dried at 150° C. to 200° C. until the moisture is completely eliminated, thereby obtaining a dried MnZn ferrite material;

[0025] In step (6), the MnZn ferrite green tape is sintered in an oxygen-controlled atmosphere at a sintering temperature of 1100° C. to 1300° C. for 2 h to 4 h.

[0026] As a preferred method, in the process of preparing the NiZn ferrite secondary layer, in step (1), the main formula of the NiZn ferrite is calculated by molar ratio as follows: Fe2O3: 49mol%~70mol%; ZnO: 4mol%-40mol%; NiO: 5mol%~40mol%, CuO: 0~10mol%, MgO: 0~50mol%, and the sub-formula components can be one or more of SnO2, CaO, TiO2, ZrO2, SiO2, V2O5, and Nb2O5; in step (2), the main formula powder is wet mixed, and deionized water with a mass ratio of 1:1 and 0.002wt%~0.004wt% of an amino dispersant are added to evenly disperse the oxides, and the mixing time is 30min.

[0027] ~60min; drying at 150℃-200℃ until the moisture is completely eliminated to obtain NiZn ferrite drying material; in step (6), the NiZn ferrite green tape is sintered in air atmosphere at a sintering temperature of 900℃~1250℃ and kept warm for 2h~6h.

[0028] In the step (7), when the coating treatment is performed, the coating material used is acrylic acid or PET, and when the fragmentation treatment is performed, the fragmentation process can be rolling, vibration, extrusion, or curling.

[0029] In the step (8), the binder between the secondary layers is a thermosetting resin adhesive.

[0030] In the step (8), the bidirectional warm pressing pressure is generally 100MPa to 300MPa, the pressure is maintained for 5s to 10s, and the resistance wire is used to keep the mold at a constant temperature of 80°C to 120°C.

[0031] In the step (9), a matrix punching die may be used for punching, or a multi-wire cutting method may be used for cutting.

[0032] In the present invention, the MnZn-based and NiZn-based magnetic sheets are sintered in a suitable atmosphere, the split sheets are coated and bonded into a composite layer, a number of composite layers are stacked, a blank is formed by warm pressing, and then it is punched or cut into a magnetic core of a certain shape. This method can avoid the problem of uneven performance caused by uneven temperature diffusion between the surface and the core of the magnetic core and uneven oxygen diffusion during sintering of a large-sized magnetic core, and is beneficial to the homogenization of the internal grain structure. The blank is punched to obtain a magnetic core of the desired shape, and a batch of magnetic cores can be punched once through mold design, saving powder filling and holding time, and reducing the amount of subsequent grinding.

[0033] Compared with the traditional ferrite production spray granulation powder making technology, since the powder particles are adhered to the surface of PVA, zinc stearate and other polymer compounds, it takes a long time to heat treat them to remove them, resulting in energy consumption. If the process is not suitable, it will also cause the core to crack and not be completely removed, thus causing problems such as low core density and many pores. The composite magnetic core preparation method provided by the present invention, since the actual ferrite production reaction has been completed in the magnetic sheet sintering stage, the magnetic core obtained by subsequent punching only needs to be heat cured and finalized. Since the matrix is ​​already a cooked ferrite composite material at this time, it is difficult for the debinding waste gas to enter the crystal to cause holes, so it has little effect on the performance of the magnetic core.

[0034] Compared with the prior art, the present invention has the following beneficial effects:

[0035] MnZn and NiZn ferrite slurries are prepared separately, and green strips with a certain thickness are cast. They can be sintered in their respective suitable atmospheres to avoid the performance deterioration caused by the atmosphere mismatch caused by the co-firing of multiple components in the traditional composite method. For example, MnZn ferrite can obtain better electromagnetic properties by sintering under an insulating oxygen partial pressure of 2vol% to 6vol%, and NiZn ferrite is suitable for sintering in an air atmosphere.

[0036] The electromagnetic properties of the final magnetic core can be controlled by adjusting the arrangement and proportion of the secondary layer ferrites of the MnZn and NiZn series. Similarly, by adjusting the ratio of the main formula and the sub-formula in the MnZn and NiZn series ferrite slurries, the purpose of adjusting the electrical properties of the secondary layer magnetic sheets can also be achieved. For example, the MnZn series secondary layer and the NiZn series secondary layer can be arranged in an ABAB manner to obtain high Bs and excellent frequency characteristics. Similarly, by changing the formula system to obtain MnZn series secondary layers with different performances, high Bs and low loss power materials can be obtained through combination, which has the characteristics of high design flexibility and customization.

[0037] When sintering a large-size magnetic core prepared by this composite method, the problem of uneven local performance of the magnetic core caused by uneven temperature diffusion and oxygen diffusion between the surface and the core can be avoided, which is beneficial to the homogenization of the grain structure inside the magnetic core.

[0038] In the process of punching the blank to obtain the magnetic core of the required shape, the mold matrix design can be used to punch out multiple magnetic cores at one time, saving powder filling and pressure holding time, and reducing the subsequent grinding amount.

[0039] Figure 1 This is a schematic diagram of the structure of the NiMnZn composite blank plate in Example 1;

[0040] Figure 2 It is a schematic diagram of the punching matrix die for the annular magnetic core;

[0041] FIG3(a) is a schematic diagram of the annular magnetic core after punching in Example 1; FIG3(b) is a cross-sectional view of the annular magnetic core after punching;

[0042] Figure 4 The graphs of the magnetic permeability of Example 1, Comparative Examples 1 and 2 as a function of frequency are shown.

[0043] Among them, 1-annular magnetic core punched out from composite blank sheet, 2-cross-sectional view of composite annular magnetic core, 3-MnZn secondary layer in composite layer, 4-NiZn secondary layer in composite layer, 5-composite layer, Figure 1 In the process, two secondary layers form a composite layer, and the composite layers are repeatedly stacked to form a composite blank plate. DETAILED DESCRIPTION

[0044] The present invention is further described below in conjunction with the embodiments. It should be noted that the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0045] Embodiment 1:

[0046] The NiMnZn composite soft ferrite core is prepared according to the following method. The schematic diagram of the composite blank structure is shown in Figure 1 .

[0047] Magnetic sheet manufacturing process:

[0048] Step (1): MnZn magnetic sheet manufacturing uses commercially available raw materials of Fe2O3 (purity ≥ 99.3%), Mn3O4 (Mn content ≥ 71%), and ZnO (purity ≥ 99.7%) to prepare the ingredients according to the main formula of Fe2O3: 52.91 mol%, ZnO: 18.84 mol%, and MnO as the balance;

[0049] Step (2): Place the prepared raw materials in a sand mill, add deionized water in a ratio of 1:1, add 5 wt% of a dispersant, mix for 15 minutes, take out the slurry and place it in a 130°C oven for drying;

[0050] Step (3): pre-sintering the dried powder in an electric resistance furnace in an air atmosphere for 2 hours at a temperature of 900° C., and then cooling the powder to room temperature before taking it out of the furnace;

[0051] Step (4): adding the sub-formula: 500ppmCaCO3, 300ppmBi2O3, 50ppmNb2O5, 500ppmTiO2 to the pre-sintered material, performing secondary ball milling to prepare pulp, adding a mixture of alcohol and ethylbenzene at a solute to solution mass ratio of 5:4, adding 0.45wt% dibutyl diformate plasticizer, 0.16wt% triethanolamine dispersant and polyvinyl butyral binder to prepare pulp, the sand milling time is 100min, and the particle size D50 is controlled at 1.0μm to 1.5μm; Step (5): casting the slurry into a green sheet with a thickness of 0.3mm, and cutting it into green sheets with a length and width of 300mm, stacking and sintering, and the number of stacking layers is 5 to 10 layers per sintered plate;

[0052] Step (6): The green strip is sintered at a sintering temperature of 1250°C and kept warm for 3 hours with an oxygen partial pressure of 3.2 vol%. It is then cooled to 120°C at a rate of 2°C / min under the equilibrium oxygen partial pressure to obtain a ferrite secondary layer magnetic sheet. Step (7): The ferrite secondary layer magnetic sheet is coated with a PET film and then curled and split. After a second split in the vertical direction, a layer of thermosetting resin adhesive is evenly applied on the bottom surface of the magnetic sheet to obtain a MnZn ferrite secondary layer magnetic sheet.

[0053] Magnetic sheet manufacturing process:

[0054] Step (1): NiZn magnetic sheet is manufactured by using commercially available raw materials of Fe2O3 (purity ≥ 99.3%), ZnO (purity ≥ 99.7%), and NiO (purity ≥ 96.6%) according to the main formula of Fe2O3: 49.67 mol%, ZnO: 31.11 mol%, and NiO as the balance;

[0055] Step (2): Place the prepared raw materials in a sand mill, add deionized water in a ratio of 1:1, add 5 wt% of a dispersant, mix for 15 minutes, take out the slurry and place it in a 130°C oven for drying;

[0056] Step (3): pre-sintering the dried powder in a resistance furnace in an air atmosphere for 2 hours at a temperature of 920° C., and then cooling the powder to room temperature before taking it out of the furnace;

[0057] Step (4): adding the sub-formula: 300ppmCaCO3, 300ppmBi2O3, 1000ppmNb2O5, 100ppmSiO2 to the pre-sintered material, performing secondary ball milling to make pulp, adding a mixture of alcohol and ethylbenzene at a solute to solution mass ratio of 5:4, adding 0.45wt% dibutyl diformate plasticizer, 0.16wt% triethanolamine dispersant and polyvinyl butyral binder to make pulp, the sand milling time is 100min, and the particle size D50 is controlled at 1.0μm to 1.5μm;

[0058] Step (5): casting the slurry into a green sheet with a thickness of 0.3 mm, and cutting it into green sheets with a length and width of 300 mm, stacking and sintering, with the number of stacking layers being 5 to 10 per sintered plate;

[0059] Step (6): the green tape is sintered at a sintering temperature of 1150° C., kept in an air atmosphere for 4 hours, cooled to 120° C. at a rate of 2° C. / min, and taken out of the furnace to obtain a ferrite secondary layer magnetic sheet;

[0060] Step (7): After coating the ferrite secondary layer magnetic sheet with a PET film, the sheet is curled and split, and after secondary splitting in the vertical direction, a layer of thermosetting resin adhesive is evenly applied on the bottom surface of the sheet to obtain a NiZn ferrite secondary layer magnetic sheet;

[0061] After the MnZn and NiZn secondary layer magnetic sheets are prepared respectively, the two are compounded, and the process is as follows:

[0062] Step (8): stacking the MnZn and NiZn magnetic sheets in an ABAB arrangement to form a ferrite composite layer, repeating the above operation to obtain a composite ferrite blank with a thickness of 3 mm, and performing warm pressing at 200 MPa at a temperature of 90° C. to obtain a highly flat and evenly bonded composite ferrite blank sheet;

[0063] Step (9): Punch the composite ferrite blank sheet into an annular magnetic core with an outer diameter of 18 mm ± 0.5 mm, an inner diameter of 8 mm ± 0.5 mm, and a height of 2.5 mm ± 0.5 mm. The schematic diagram of the annular magnetic core punching matrix mold used is shown in Figure 2 The schematic diagram of the annular core after punching is shown in Figure 3(a), and the cross-sectional view of the annular core is shown in Figure 3(b). The core was placed in an oven for heat curing for 30 minutes at a temperature of 80°C. After cooling and placing for 24 hours, its magnetic permeability versus frequency curve and saturation flux density were tested.

[0064] Comparative Example 1:

[0065] Step (1): MnZn magnetic sheet manufacturing uses commercially available raw materials of Fe2O3 (purity ≥ 99.3%), Mn3O4 (Mn content ≥ 71%), and ZnO (purity ≥ 99.7%) to prepare the ingredients according to the main formula of Fe2O3: 52.91 mol%, ZnO: 18.84 mol%, and MnO as the balance;

[0066] Step (2): Place the prepared raw materials in a sand mill, add deionized water in a ratio of 1:1, add 5 wt% of a dispersant, mix for 15 minutes, take out the slurry and place it in a 130°C oven for drying;

[0067] Step (3): pre-sintering the dried powder in an electric resistance furnace in an air atmosphere for 2 hours at a temperature of 900°C, followed by cooling to room temperature before being taken out of the furnace;

[0068] Step (4): adding the sub-formula: 500ppmCaCO3, 300ppmBi2O3, 50ppmNb2O5, 500ppmTiO2 to the pre-sintered material, performing secondary ball milling to prepare pulp, adding a mixture of alcohol and ethylbenzene at a solute to solution mass ratio of 5:4, adding 0.45wt% dibutyl diformate plasticizer, 0.16wt% triethanolamine dispersant and polyvinyl butyral binder to prepare pulp, the sand milling time is 100min, and the particle size D50 is controlled at 1.0μm to 1.5μm; Step (5): casting the slurry into a green sheet with a thickness of 0.3mm, and cutting it into green sheets with a length and width of 300mm, stacking and sintering, and the number of stacking layers is 5 to 10 layers per sintered plate;

[0069] Step (6): sintering the green strip at a sintering temperature of 1250° C., keeping the temperature for 3 hours, keeping the oxygen partial pressure at 3.2 vol%, cooling to 120° C. at a rate of 2° C. / min under the equilibrium oxygen partial pressure, and obtaining a ferrite magnetic sheet;

[0070] Step (7): After the ferrite magnetic sheet is coated with a PET film, it is curled and split, and after secondary splitting in the vertical direction, a layer of thermosetting resin adhesive is evenly applied on the bottom surface of the magnetic sheet to obtain a MnZn ferrite secondary layer magnetic sheet;

[0071] Step (8): stacking the MnZn magnetic sheets to obtain a ferrite blank with a thickness of 3 mm, and performing warm pressing at 200 MPa and a temperature of 90° C. to obtain a highly flat and evenly bonded MnZn ferrite blank sheet;

[0072] Step (9): Same as Example 1.

[0073] Comparative Example 2:

[0074] Step (1): NiZn magnetic sheet is manufactured by using commercially available raw materials of Fe2O3 (purity ≥ 99.3%), ZnO (purity ≥ 99.7%), and NiO (purity ≥ 96.6%) according to the main formula of Fe2O3: 49.67 mol%, ZnO: 31.11 mol%, and NiO as the balance;

[0075] Step (2): Place the prepared raw materials in a sand mill, add deionized water in a ratio of 1:1, add 5 wt% of a dispersant, mix for 15 minutes, take out the slurry and place it in a 130°C oven for drying;

[0076] Step (3): pre-sintering the dried powder in a resistance furnace in an air atmosphere for 2 hours at a temperature of 920° C., and then cooling the powder to room temperature before taking it out of the furnace;

[0077] Step (4): adding the sub-formula: 300ppmCaCO3, 300ppmBi2O3, 1000ppmNb2O5, 100ppmSiO2 to the pre-sintered material, performing secondary ball milling to make pulp, adding a mixture of alcohol and ethylbenzene at a solute to solution mass ratio of 5:4, adding 0.45wt% dibutyl diformate plasticizer, 0.16wt% triethanolamine dispersant and polyvinyl butyral binder to make pulp, the sand milling time is 100min, and the particle size D50 is controlled at 1.0μm to 1.5μm;

[0078] Step (5): casting the slurry into a green sheet with a thickness of 0.3 mm, and cutting it into green sheets with a length and width of 300 mm, stacking and sintering, with the number of stacking layers being 5 to 10 per sintered plate;

[0079] Step (6): the green strip is sintered at a sintering temperature of 1150°C, kept in an air atmosphere for 4 hours, cooled to 120°C at a rate of 2°C / min, and taken out of the furnace to obtain a ferrite magnetic sheet;

[0080] Step (7): After the ferrite magnetic sheet is coated with a PET film, it is rolled and split, and after secondary splitting in the vertical direction, a layer of thermosetting resin adhesive is evenly applied on the bottom surface of the magnetic sheet;

[0081] Step (8): stacking the NiZn magnetic sheets to obtain a ferrite blank with a thickness of 3 mm, and performing warm pressing at 200 MPa and a temperature of 90° C. to obtain a highly flat and uniformly bonded NiZn ferrite blank sheet;

[0082] Step (9): Same as in Example 1. Figure 4 As shown in the figure, the permeability frequency characteristic of the MnZn+NiZn composite core is between that of MnZn ferrite and NiZn ferrite. The Bs value is 387mT as shown in Table 1, which is also between that of MnZn and NiZn ferrite. While taking into account the frequency characteristic, the Bs value is 20% higher than that of the NiZn ferrite core.

[0083] Table 1 Comparison of composite core and single material core Bs

[0084]

[0085]

[0086] Embodiment 2:

[0087] The MnZn composite soft ferrite core was prepared according to the following method:

[0088] MnZn ferrite type A magnetic sheet manufacturing process:

[0089] Step (1): using commercially available raw materials of Fe2O3 (purity ≥ 99.3%), Mn3O4 (Mn content ≥ 71%), and ZnO (purity ≥ 99.7%), and preparing the ingredients according to the main formula of Fe2O3: 53.28 mol%, ZnO: 10.84 mol%, and Mn3O4 as the balance;

[0090] Step (2): Place the prepared raw materials in a sand mill, add deionized water in a ratio of 1:1, add 5 wt% of a dispersant, mix for 15 minutes, take out the slurry and place it in a 130°C oven for drying;

[0091] The dried powder is pre-fired in a resistance furnace in an air atmosphere for 2 hours at a temperature of 900°C, and then cooled to room temperature before being taken out of the furnace.

[0092] Step (3): adding the sub-formula: 800ppmCaCO3, 150ppmNb2O5, 200ppmZrO2, 4500ppmCo2O3 to the pre-sintered material, performing secondary ball milling to prepare pulp, adding a mixture of alcohol and ethylbenzene at a solute to solution mass ratio of 5:4, adding 0.45wt% dibutyl diformate plasticizer, 0.16wt% triethanolamine dispersant and polyvinyl butyral binder to prepare pulp, the sand milling time is 100min, and the particle size D50 is controlled at 1.0μm to 1.5μm;

[0093] Step (4): casting the slurry into a green sheet with a thickness of 0.3 mm, and cutting it into green sheets with a length and width of 300 mm, stacking and sintering, with the number of stacking layers being 5 to 10 per sintered plate;

[0094] Step (5): The green strip is sintered at a sintering temperature of 1260°C, kept warm for 3 hours with an oxygen partial pressure of 4.5 vol%, and cooled to 120°C at a rate of 2°C / min under equilibrium oxygen partial pressure to obtain a ferrite secondary layer magnetic sheet blank; Step (6): The ferrite secondary layer magnetic sheet blank is coated with a PET film and then curled and split. After a second split in the vertical direction, a layer of thermosetting resin adhesive is evenly applied to the bottom surface of the magnetic sheet.

[0095] MnZn ferrite type B magnetic sheet manufacturing process:

[0096] Step (1): Use commercially available raw materials of Fe2O3 (purity ≥ 99.3%), Mn3O4 (Mn content ≥ 71%), ZnO (purity ≥ 99.7%), and NiO (purity ≥ 96.6%), and prepare the materials according to the main formula of Fe2O3: 55.5mol%, ZnO: 10.5mol%, NiO: 3.8mol%, and the balance Mn3O4. Place the prepared raw materials in a sand mill, add deionized water in a ratio of 1:1, add 5wt% of dispersant, mix for 15 minutes, take out the slurry and place it in a 130°C oven for drying;

[0097] Step (2): pre-sintering the dried powder in a resistance furnace in an air atmosphere for 2 hours at a temperature of 920° C., and then cooling the powder to room temperature before taking it out of the furnace;

[0098] Step (3): adding the sub-formula: 500ppmCaCO3, 300ppmZrO2, 150ppmNb2O5, 100ppmV2O5, 60ppmSiO2 to the pre-sintered material, performing secondary ball milling to make pulp, adding a mixture of alcohol and ethylbenzene at a solute to solution mass ratio of 5:4, adding 0.45wt% dibutyl diformate plasticizer, 0.16wt% triethanolamine dispersant and polyvinyl butyral binder to make pulp, the sand milling time is 100min, and the particle size D50 is controlled at 1.0μm to 1.5μm;

[0099] Step (4): casting the slurry into a green sheet with a thickness of 0.3 mm, and cutting it into green sheets with a length and width of 300 mm, stacking and sintering, with the number of stacking layers being 5 to 10 per sintered plate;

[0100] Step (5): the green strip is sintered at a sintering temperature of 1150°C, kept in an air atmosphere for 4 hours, cooled to 120°C at a rate of 2°C / min, and taken out of the furnace to obtain a ferrite secondary layer magnetic sheet;

[0101] Step (6): After the ferrite secondary layer magnetic sheet is coated with a PET film, it is curled and split, and after secondary splitting in the vertical direction, a layer of thermosetting resin adhesive is evenly applied on the bottom surface of the magnetic sheet.

[0102] MnZn ferrite type A magnetic sheets and type B magnetic sheets are stacked in an ABAB arrangement to form a ferrite composite layer. The above operation is repeated to obtain a composite ferrite blank with a thickness of 8 mm. The blank is warm pressed at 200 MPa at a temperature of 90°C to obtain a highly flat and evenly bonded composite ferrite blank sheet.

[0103] Comparative Example 3:

[0104] Step (1): MnZn ferrite type A magnetic sheet manufacturing uses commercially available raw materials of Fe2O3 (purity ≥ 99.3%), Mn3O4 (Mn content ≥ 71%), and ZnO (purity ≥ 99.7%), and mixes the ingredients according to the main formula of Fe2O3: 53.28 mol%, ZnO: 10.84 mol%, and Mn3O4 as the balance. The prepared raw materials are placed in a sand mill, deionized water is added in a ratio of 1:1, 5 wt% of a dispersant is added, and after mixing for 15 minutes, the slurry is taken out and placed in a 130°C oven for drying;

[0105] Step (2): pre-sintering the dried powder in an electric resistance furnace in an air atmosphere for 2 hours at a temperature of 900° C., and then cooling the powder to room temperature before taking it out of the furnace;

[0106] Step (3): adding the sub-formula: 800ppmCaCO3, 150ppmNb2O5, 200ppmZrO2, 4500ppmCo2O3 to the pre-sintered material, performing secondary ball milling to prepare pulp, adding a mixture of alcohol and ethylbenzene at a solute to solution mass ratio of 5:4, adding 0.45wt% dibutyl diformate plasticizer, 0.16wt% triethanolamine dispersant and polyvinyl butyral binder to prepare pulp, the sand milling time is 100min, and the particle size D50 is controlled at 1.0μm to 1.5μm;

[0107] Step (4): casting the slurry into a green sheet with a thickness of 0.3 mm, and cutting it into green sheets with a length and width of 300 mm, stacking and sintering, with the number of stacking layers being 5 to 10 per sintered plate;

[0108] Step (5): sintering the green tape at a sintering temperature of 1260°C, keeping it warm for 3 hours, keeping the oxygen partial pressure at 4.5 vol%, cooling it to 120°C at a rate of 2°C / min under the equilibrium oxygen partial pressure, and obtaining a ferrite secondary layer magnetic sheet blank; Step (6): coating the ferrite secondary layer magnetic sheet blank with a PET film, curling and splitting it, performing secondary splitting in the vertical direction, and evenly applying a layer of thermosetting resin adhesive on the bottom surface of the magnetic sheet;

[0109] Step (7): MnZn ferrite type A magnetic sheets are stacked to obtain a composite ferrite blank with a thickness of 8 mm, and warm pressed at 200 MPa and a temperature of 90° C. to obtain a highly flat and evenly bonded composite ferrite blank sheet.

[0110] Comparative Example 4:

[0111] Step (1): MnZn ferrite type B magnetic sheet is manufactured by using commercially available raw materials of Fe2O3 (purity ≥ 99.3%), Mn3O4 (Mn content ≥ 71%), ZnO (purity ≥ 99.7%), and NiO (purity ≥ 96.6%), and the ingredients are prepared according to the main formula of Fe2O3: 55.5mol%, ZnO: 10.5mol%, NiO: 3.8mol%, and the balance Mn3O4;

[0112] Step (2): Place the prepared raw materials in a sand mill, add deionized water in a ratio of 1:1, add 5wt% of dispersant, mix for 15 minutes, take out the slurry and place it in a 130℃ oven for drying. Pre-sinter the dried powder in a resistance furnace, the pre-sintering atmosphere is air, the time is 2h, the temperature is 920℃, and then it is cooled to room temperature and taken out of the furnace;

[0113] Step (3): adding the sub-formula: 500ppmCaCO3, 300ppmZrO2, 150ppmNb2O5, 100ppmV2O5, 60ppmSiO2 to the pre-sintered material, performing secondary ball milling to make pulp, adding a mixture of alcohol and ethylbenzene at a solute to solution mass ratio of 5:4, adding 0.45wt% dibutyl diformate plasticizer, 0.16wt% triethanolamine dispersant and polyvinyl butyral binder to make pulp, the sand milling time is 100min, and the particle size D50 is controlled at 1.0μm to 1.5μm;

[0114] Step (4): casting the slurry into a green sheet with a thickness of 0.3 mm, and cutting it into green sheets with a length and width of 300 mm, stacking and sintering, with the number of stacking layers being 5 to 10 per sintered plate;

[0115] Step (5): the green strip is sintered at a sintering temperature of 1150°C, kept in an air atmosphere for 4 hours, cooled to 120°C at a rate of 2°C / min, and taken out of the furnace to obtain a ferrite secondary layer magnetic sheet;

[0116] Step (6): Covering the ferrite secondary layer magnetic sheet with a PET film, curling and splitting the sheet, splitting the sheet twice in the vertical direction, and evenly applying a layer of thermosetting resin adhesive on the bottom surface of the sheet;

[0117] Step (7): MnZn ferrite type B magnetic sheets are stacked to obtain a composite ferrite blank with a thickness of 8 mm, and warm pressed at 200 MPa and a temperature of 90° C. to obtain a highly flat and evenly bonded composite ferrite blank sheet.

[0118] The ferrite blank sheets obtained in Example 2 and Comparative Examples 3 and 4 were punched into annular magnetic cores with an outer diameter of 25 mm ± 0.5 mm, an inner diameter of 15 mm ± 0.5 mm, and a height of 7.5 mm ± 0.5 mm. The magnetic cores were placed in an oven for heat curing for 30 minutes at a temperature of 80°C. After cooling and placing for 24 hours, the loss versus temperature curve and the saturation magnetic flux density were tested.

[0119] As shown in Table 2, although the power consumption of the composite core in Example 2 is higher than that of the first-class material MnZn ferrite, it is significantly better than that of the second-class material, and the Bs is higher than that of the first-class core, taking into account the wide temperature, low power consumption and high Bs characteristics.

[0120] Table 2 Performance comparison of composite core and single material core

[0121]

[0122]

Claims

1. A method for preparing a multilayer composite soft ferrite core, characterized in that: The multi-layer composite soft ferrite core is formed by stacking two or more soft ferrite composite layers, and a single soft ferrite composite layer is composed of two or more soft ferrite secondary layers. The electromagnetic properties of the composite layer can be adjusted by changing the main formula and sub-formula of the soft ferrite secondary layer in the composite layer, the manufacturing process of the secondary layer ferrite pre-sintering material, the arrangement of the secondary layer and the proportion of the composite layer, so as to further improve the electromagnetic properties of the core; The preparation method of the multi-layer composite soft ferrite core is as follows: first, two or more ferrite secondary layers are prepared, which are formed after molding, sintering and laminating processes, then, the two or more secondary layers are bonded to obtain a soft ferrite composite layer, the two or more soft ferrite composite layers are stacked and pressed into a blank, and finally, the blank is punched or cut, heat-treated and cured to prepare a multi-layer composite soft ferrite core; First, two or more ferrite secondary layers are determined, and then the magnetic core is prepared according to the following method, including: Step (1): preparing ingredients according to the main formula and the sub-formula of the ferrite secondary layer; Step (2): wet-mixing the main formula powders and then drying them to obtain ferrite dried materials; Step (3): pre-sintering the dried ferrite materials obtained in step (2) in an air atmosphere at a temperature of 800° C. to 1000° C. for 2 h to 4 h, and cooling to room temperature in the furnace to obtain two or more ferrite pre-sintered materials; Step (4): the ferrite pre-fired materials pre-fired in step (3) are respectively subjected to ball milling, and a mixed solvent of alcohol and ethylbenzene is added in a mass ratio of solute to solvent of 5:

4. After ball milling for 2 hours, a dispersant, a plasticizer, and a binder are added, and then the sub-formula components are added and ball milled together with the main formula for 6 hours to 10 hours to prepare a slurry with a viscosity of 40000mPa.s to 60000mPa.s. The ball milling time is controlled to make the particle size distribution D50: 1μm to 2.5μm; Step (5): preparing the ferrite slurry into ferrite green tapes with a smooth surface and a thickness of 0.1 mm to 0.5 mm by tape casting process; Step (6): sintering the ferrite green strips separately, heating to 900°C to 1300°C at a rate of 3°C / min to 5°C / min, and then keeping the temperature for 2h-6h, with an oxygen partial pressure of 2vol% to 20vol%. In the cooling stage, the temperature is cooled to below 200°C at a cooling rate of 2°C / min to 4°C / min using a balanced oxygen partial pressure method, and then the temperature is removed from the furnace to obtain two or more ferrite secondary layer magnetic sheets; Step (7): coating and splitting the ferrite secondary layer magnetic sheet blanks sintered in step (6) to obtain two or more ferrite secondary layer magnetic sheets; Step (8): bonding two or more ferrite secondary layer magnetic sheets obtained in step (7) with an adhesive to obtain a ferrite composite layer, stacking the two or more composite layers together, and pressing them into a composite soft ferrite blank plate by bidirectional warm pressing; Step (9): Punch or cut the composite soft ferrite blank sheet obtained in step (8) into a magnetic core, and then perform a heat curing treatment to obtain a multilayer composite ferrite magnetic core.

2. The method for preparing a multilayer composite soft ferrite core according to claim 1, characterized in that: The ferrite secondary layer may be MnZn ferrite or NiZn ferrite.

3. The method for preparing a multilayer composite soft ferrite core according to claim 2, characterized in that: In the process of preparing the MnZn ferrite secondary layer, in step (1), the main formula is calculated by molar ratio as follows: Fe2O3: 48mol% to 58mol%; ZnO: 3mol% to 25mol%; the balance is Mn3O4, and the sub-formula components can be one or more of SnO2, CaO, TiO2, ZrO2, SiO2, V2O5, and Nb2O5; In step (2), deionized water is added in a mass ratio of 1:1, and an amino dispersant is added to mix the oxides evenly to prevent agglomeration, and the mixing time is 15 min to 30 min; the mixture is dried at 150° C. to 200° C. until the moisture is completely eliminated, thereby obtaining a dried MnZn ferrite material; In step (6), the MnZn ferrite green tape is sintered in an oxygen-controlled atmosphere at a sintering temperature of 1100° C. to 1300° C. for 2 h to 4 h.

4. The method for preparing a multilayer composite soft ferrite core according to claim 2, characterized in that: In the process of preparing the NiZn ferrite secondary layer, in step (1), the main formula of the NiZn ferrite is calculated by molar ratio: Fe2O3: 49 mol% to 70 mol%; ZnO: 4mol% to 40mol%; NiO: 5mol% to 40mol%, CuO: 0mol% to 10mol%, MgO: 0mol% to 50mol%, and the secondary ingredients may be one or more of SnO2, CaO, TiO2, ZrO2, SiO2, V2O5, and Nb2O5; In step (2), the main formula powder is wet mixed, and deionized water and 0.002wt% to 0.004wt% of an amino dispersant are added in a mass ratio of 1:1 to evenly disperse the oxides, and the mixing time is 30min to 60min; the mixture is dried at 150°C to 200°C until the moisture is completely eliminated, thereby obtaining a NiZn-based ferrite dried material; In step (6), the NiZn-based ferrite green tape is sintered in an air atmosphere at a sintering temperature of 900° C. to 1250° C. for 2 h to 6 h.

5. The method for preparing a multilayer composite soft ferrite core according to claim 1, characterized in that: In the step (7), when the lamination process is performed, the lamination material used is acrylic acid or PET.

6. The method for preparing a multilayer composite soft ferrite core according to claim 1, characterized in that: In the step (7), the splitting process can adopt one or more of the methods of rolling, vibration, extrusion and curling.

7. The method for preparing a multilayer composite soft ferrite core according to claim 1, characterized in that: In the step (8), the binder between the secondary layers is a thermosetting resin adhesive.

8. The method for preparing a multilayer composite soft ferrite core according to claim 1, characterized in that: In the step (8), the bidirectional warm pressing pressure is generally 100MPa to 300MPa, the pressure is maintained for 5s to 10s, and the resistance wire is used to keep the mold at a constant temperature of 80°C to 120°C.

9. The method for preparing a multi-layer composite soft ferrite core according to claim 1, characterized in that: In the step (9), a matrix punching die may be used for punching, or a multi-wire cutting method may be used for cutting.

Citation Information

Patent Citations

  • Composite soft magnetic material and method for preparing material

    CN103632794A

  • Magnetic Grain Boundary Engineered Ferrite Core Materials

    CN103765524B

  • Controllable preparation method of array-type wireless charging magnetic conductive sheets

    CN110098043A

  • Magnetic core and preparation method thereof, inductor and filter

    CN111584206A